STRATEGI PENERAPAN PRINSIP ARSITEKTUR BIOKLIMATIK PADA IKLIM TROPIS TERHADAP KENYAMANAN TERMAL DAN EFISIENSI ENERGI BANGUNAN - Nabila Permatasari (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Global climate change has become a serious challenge that affects various aspects of life, including the field of architecture, especially in tropical climates. Increasing environmental temperatures and changing weather patterns have a significant impact on the thermal comfort and energy efficiency of buildings. This article aims to explain strategies for applying bioclimatic architectural principles as design solutions that are responsive to local climate conditions. Through systematic literature analysis, it was found that architectural design that considers climatic factors can increase comfort for occupants and reduce dependence on artificial lighting and lighting systems. This article also discusses various strategies for applying bioclimatic principles, such as the placement of the building's core orientation, window openings, balconies, transitional spaces, wall design, landscape relationships, passive shading, and heat insulation on the floor, where the application of these strategies can help create a more beautiful building. sustainable and energy efficient. Therefore, the application of bioclimatic architecture is very important to create buildings that can adapt well and efficiently in tropical areas.